Human Resource Management at Filantropi School: Paternalistic Leadership in Mitigating Burnout and Maintaining Teacher Commitment - Irnie Victorynie; Ronaldi Saleh Bin Umar (Sakura Digital Nusantara, 2026)
This research aims to explore human resource management strategies in maintaining teacher commitment and mitigating burnout risks within philanthropic educational institutions. The study focuses on a free elementary school experiencing a significant surge in student enrollment despite offering non-competitive financial compensation. Using a qualitative approach with an intrinsic case study design, data were collected through in-depth interviews with the Chairman of the Foundation, the Principal, and teachers with more than ten years of service. Data validity was ensured through source triangulation. The results indicate that organizational commitment is built through the internalization of transcendental values and paternalistic leadership. The Chairman serves as a nurturing figure providing emotional support and psychological safety as a substitute for financial incentives. Although the workload increased due to high student participation, burnout risks were effectively mitigated through a familial work climate and a profound sense of meaning in work. These findings imply that value-oriented and empathetic leadership is a crucial instrument for the sustainability of community-based schools amidst fiscal constraints.